2021
DOI: 10.1007/s11664-020-08708-4
|View full text |Cite
|
Sign up to set email alerts
|

Growth Parameter Based Control of Cation Disorder in MgSnN2 Thin Films

Abstract: MgSnN 2 thin films have been grown on yttria-stabilized zirconia substrates via plasma-assisted molecular beam epitaxy and analyzed using reflection high-energy electron diffraction, X-ray diffraction, optical transmission, and cathodoluminescence. By systematically varying the growth parameters, particularly the substrate temperature, Mg:Sn flux ratio, substrate, and nitrogen flow rate, we were able to achieve high quality films and control disorder in the cation sublattice. This control of disorder allows fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…Another first-principles study reported a reduced E g of 2.69 eV in cation-disordered rs-MTN . These facts suggest that the cation disorder in rs-MgSnN 2 leads to a reduction in E g as with the cases of WZ-type ZnSnN 2 and MgSnN 2 . ,, The experimental E g opt value in this study is close to the latter-predicted value and consistent with the previously estimated E g opt value of 2.3–2.4 eV in rs-MTN powders with a disordered cation sublattice. , Thus, we speculate that the directly grown rs-MTN film obtained in this study had a disordered cation sublattice. However, these E g opt comparisons are insufficient to conclude that the cation sublattice in the rs-MTN film was fully disordered.…”
Section: Results and Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Another first-principles study reported a reduced E g of 2.69 eV in cation-disordered rs-MTN . These facts suggest that the cation disorder in rs-MgSnN 2 leads to a reduction in E g as with the cases of WZ-type ZnSnN 2 and MgSnN 2 . ,, The experimental E g opt value in this study is close to the latter-predicted value and consistent with the previously estimated E g opt value of 2.3–2.4 eV in rs-MTN powders with a disordered cation sublattice. , Thus, we speculate that the directly grown rs-MTN film obtained in this study had a disordered cation sublattice. However, these E g opt comparisons are insufficient to conclude that the cation sublattice in the rs-MTN film was fully disordered.…”
Section: Results and Discussionsupporting
confidence: 89%
“…54 These facts suggest that the cation disorder in rs-MgSnN 2 leads to a reduction in E g as with the cases of WZ-type ZnSnN 2 and MgSnN 2 . 16,21,55 The experimental E g opt value in this study is close to the latterpredicted value and consistent with the previously estimated E g opt value of 2.3−2.4 eV in rs-MTN powders with a disordered cation sublattice. 17,18 Thus, we speculate that the directly grown rs-MTN film obtained in this study had a disordered cation sublattice.…”
Section: Direct Growth Of Rs-mtn On Mgo(111)supporting
confidence: 91%
See 1 more Smart Citation
“…In the past decade, researchers have begun to investigate wurtzite-type II–IV–N 2 nitrides, including ZnSnN 2 , Zn­(Ge,Sn)­N 2 , and MgSnN 2 , as semiconductors for photovoltaics and light emitters. The cations in the sputtered ZnSnN 2 and MgSnN 2 films almost randomly occupy the cation sublattice in the wurtzite structure (disordered wurtzite structure), , as shown in Figure a (the crystal structure was visualized using the software VESTA).…”
Section: Introductionmentioning
confidence: 99%
“…(b) Dependence of the band gap ( E g ) on the hexagonal lattice constant for III-, Zn–IV-, and Mg–IV-nitrides. The data were obtained from the literature (ref for AlN, GaN, InN, ZnSiN 2 , and ZnGeN 2 , refs and for ZnSnN 2 , ref for MgSnN 2 , and ref for MgSiN 2 and MgGeN 2 ).…”
Section: Introductionmentioning
confidence: 99%